DIPLOMASI KEBUDAYAAN OCAS (ORQUESTA DA CAMARA DE SIERO) DALAM MEMPROMOSIKAN MUSIK SPANYOL DI INDONESIA MELALUI KEGIATAN VINCULOS 2017 - Khashaaisha Oktiapani; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this research is to find out how the role of OCAS (Orquesta Da Camara De Siero) in conducting diplomacy through the promotion of Spanish music at Vinculos Indonesia 2017. Vinculos is one of the activities owned by OCAS, which is run annually to spread tolerance between ethnic, religious and cultural In addition, this activity is intended to introduce orchestras to remote areas, provide rehabilitation assistance through music, present and help develop music in schools and make good relations with fellow musicians around the world.This research uses a pluralism perspective. Pluralism believes that the state is not the only actor in the international world. This research is also guided by the theory of Cultural Diplomacy and the Soft Power Concept. The method used is a qualitative method. Data interview techniques and literature studies from several journals, books, documents and websites.This study shows the activities carried out by OCAS while in Indonesia in the Vinculos 2017 activities. Diplomacy carried out by OCAS in Indonesia uses the form of diplomacy in the form of exhibitions, negotiations and conferences. The forms of diplomacy that have been carried out by OCAS have resulted in good relations between OCAS and the Indonesian government and the Indonesian people. so there are follow-up activities for Vinculos 2018 and Vinculos 2019. Keywords : OCAS, Vinculos 2017, Indonesia.